Trajectories of Illness Intrusiveness Domains Following a Diagnosis of Breast Cancer - Sohl, Stephanie J. (2013)
OBJECTIVE: To identify trajectories of illness intrusiveness over the first two years following a breast cancer diagnosis and describe associated patient and treatment characteristics. Illness intrusiveness, or how much an illness disrupts life domains, has been shown to be highly related to quality of life. METHODS: Women recruited within 8 months of a breast cancer diagnosis (n=653) completed questionnaires at baseline and 6, 12, and 18 months post baseline. Group-based trajectory modeling was used to identify trajectories in three established domains of illness intrusiveness: instrumental, intimacy, and relationships and personal development. Bivariate analyses identified contextual, disease/treatment, psychological and social characteristics of women in trajectory groups. RESULTS: Forty-one percent of women fell into a trajectory of consistently low illness intrusiveness (Low) across all three domains. Other women varied such that some reported illness intrusiveness that decreased over time on at least one domain (9-34%), and others reported consistently high intrusiveness on at least one domain (11-17%). A fourth trajectory of increased illness intrusiveness emerged in the relationship and personal development domain (9%). Characteristics of women in the Low group were older, less likely to have children at home, stage I cancer, fewer symptoms, and better psychosocial status. CONCLUSIONS: Women experienced different patterns of illness intrusiveness in the first two years following a diagnosis of breast cancer with a high percentage reporting Low intrusiveness. However, women differentially followed the other trajectory patterns by domain, suggesting that the impact of breast cancer on some women’s lives may be specific to certain areas.